Viral surveillance using PCR during treatment of AML and ALL. Issue 1 (9th August 2017) - Dixon, Stephanie B.; Lane, Adam; O'Brien, Maureen M.; Burns, Karen C.; Mangino, Jennifer L.; Breese, Erin H.; Absalon, Michael J.; Perentesis, John P.; Phillips, Christine L.
Abstract: Background: While viral surveillance of cytomegalovirus (CMV), Epstein–Barr virus (EBV), and adenovirus using PCR is routine in patients undergoing hematopoetic stem cell transplant and solid organ transplant, the utility in the nontransplant pediatric leukemia population is unknown. Our institution screens patients with acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML) for viral DNAemia by PCR as part of clinical care. Procedure: This retrospective chart review included patients treated for newly diagnosed or relapsed AML or ALL between April 2010 and September 2014. We retrieved data for viral PCR screening, detection and quantification, duration of positivity, and prophylaxis or treatment. Results: One hundred eleven patients were included in analyses. Forty (36.0%) had at least one blood PCR positive for EBV, CMV, or adenovirus. Patients with ALL had significantly higher rates of persistent viral detection and treatment than those with AML ( P < 0.02, P < 0.01, respectively). International patients had significantly higher rates of viral detection ( P < 0.01), persistence ( P < 0.01), any treatment ( P < 0.03), and antiviral treatment ( P < 0.01); 16.9% of patients who received intravenous immunoglobulin (IVIG) prophylactically had viral detection compared to 63% of patients who did not receive prophylactic IVIG ( P = 0.0008). Conclusions: Patients with ALL were more susceptible than those with AML to viral reactivation that was persistent or resulted in treatment. Patients with relapsed ALL, refractory ALL, or infantile ALL are most likely to benefit from asymptomatic screening for CMV and adenovirus. International patients are at higher risk for reactivation and may merit screening. EBV reactivation was not significant and does not warrant screening.